Fabrication of transparent ITO/GTO bilayer diode thin films - Sutan Chairul, Imran; Echimoto, Atsushi; Tazawa, Ryutaro; Murai, Kei-ichiro; Moriga, Toshihiro (World Scientific Publishing Co Pte Ltd, 2023)
Transparent diodes were fabricated by layering a Ga–Sn–O (GTO) film onto an In2O3:Sn (ITO) film using a facing-targeted DC sputtering method. When a GTO film containing∼25 mol% Ga was deposited on the surface of the conductive ITO film at room temperature, a diode bilayer film was obtained. The bilayer film exhibited rectification characteristics of approximately 0 and 3.8 µA/V when negative and positive voltages were applied, respectively. However, the rectification characteristics increased up to 68.3 µA/V in the positive voltage applied region after annealed at 200◦C.